Deindustrialisation – A European Assessment - Michael Grömling; Michelle Koenen; Gero Kunath; Thomas Obst; Sandra Parthie (Intereconomics, 2023)
The war in Ukraine has exacerbated pre-existing production problems in manufacturing networks originating from the coronavirus pandemic. Material shortages are compounded by uncertainties about sufficient energy supplies. Above all, energy has become more expensive for European industrial companies. All this has raised the question of whether permanent changes in economic structures will occur in the wake of these geo-economic burdens. Nevertheless, European economies differ significantly in their manufacturing shares, in the importance of energy-intensive industries and in their energy supply. Based on a survey of members of AIECE, an association of European economic research institutes, the risk of deindustrialisation in Europe is assessed. Thirteen out of 20 AIECE institutes stated that they do not expect the current energy problems and the associated price effects to have a permanent impact on the economic structure of their own country. However, the institutes also point out that structural changes may occur because energy-intensive industries may relocate to non-European countries. In contrast, relocation effects within Europe are estimated to be negligible.
Keywords: F5; L52; 330